1989
DOI: 10.1007/bf00314338
|View full text |Cite
|
Sign up to set email alerts
|

Radiological studies of the cheiro-oral syndrome

Abstract: Four cases of the cheiro-oral syndrome are reported, with a review of the clinical symptoms and signs and the neuroradiological methods used to demonstrate the responsible lesion. In each case, angiography, computed tomography (CT) and magnetic resonance imaging (MRI) were performed. The lesion was found in the thalamus in three cases and in the pons in one. Infarction had occurred in three cases and haemorrhage in one. Angiography revealed normal findings in all cases. CT at the onset of the symptoms demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Pure sensory deficit with a cheirooral topography usually occurs as a result of a vascular lesion, either hemorrhage or infarction, in the region of the ventralis posterior nucleus of the thalamus 1 -7 and in the brain stem sensory pathways projecting to this nucleus. 7 - 11 In a large survey of pure sensory stroke, Fisher 12 analyzed the patterns of distribution of paresthesias and suggested that selective involvement of some, rather than all, fingers indicated a cortical localization, whereas a thalamic lesion typically caused involvement of all fingers indiscriminately.…”
mentioning
confidence: 99%
“…Pure sensory deficit with a cheirooral topography usually occurs as a result of a vascular lesion, either hemorrhage or infarction, in the region of the ventralis posterior nucleus of the thalamus 1 -7 and in the brain stem sensory pathways projecting to this nucleus. 7 - 11 In a large survey of pure sensory stroke, Fisher 12 analyzed the patterns of distribution of paresthesias and suggested that selective involvement of some, rather than all, fingers indicated a cortical localization, whereas a thalamic lesion typically caused involvement of all fingers indiscriminately.…”
mentioning
confidence: 99%
“…The cheiro-oral syndrome is defined as a sensory involvement of the central perioral part of the face and the hand, sometimes up to the distal forearm [1], without motor im pairment [2], The responsible lesion is often thalamic [2][3][4], rarely in the brain stem [5.6] or in the parietal lobe (7)(8)(9). We report one case of cheiro-oral syndrome following a vas cular parietal lesion.…”
mentioning
confidence: 99%
“…It has also been described in association with small intracerebral hemorrhages [2, 3], including a few located in the brainstem [4, 5, 6, 7, 8, 9, 10, 11, 12]. The sensory loss may involve the entire or a part of the hemibody, or have a cheiro-oral distribution [5, 7, 9, 10], being limited to the hand and the mouth or the perioral area of the same side. This particular distribution is related to damage to a restricted sector of fibers of the trigeminothalamic tract.…”
Section: Untitledmentioning
confidence: 99%
“…A few pure sensory strokes due to brainstem hematomas have been reported [4, 5, 6, 7, 8, 9, 10, 11, 12], including four with a cheiro-oral distribution of the sensory loss [5, 7, 9, 10]. As in the case described by Tuttle and Reinmuth [4], our patient had an unique distribution of the objective sensory disturbance that was limited to the palm of the hand and the retroauricular region, in the territory of the lesser occipital nerve.…”
Section: Untitledmentioning
confidence: 99%